The Substantive Rights of Heirs and Administrative Barriers in Indonesian Banking Practices - La Ode, Muhamad Taufik; Abdullah, Ali (Candela Edutech Indonesia, 2025)
This article explores the normative-institutional discrepancy between the declarative nature of Article 833 of the Indonesian Civil Code and the administrative practices of financial institutions in the execution of inheritance rights within Indonesia’s national legal system. Legally, heirs acquire their rights automatically upon the decedent’s death, without requiring court confirmation or formal recognition. In practice, however, banks often impose excessive procedural requirements, such as requesting additional documents or withholding funds without a clear legal basis. This study adopts a normative legal method, analyzing statutory provisions, doctrinal interpretations, and illustrative case studies. The findings highlight the urgent need for regulatory harmonization between inheritance law and financial administrative procedures in Indonesia. The article also emphasizes the strategic role of notaries as legal intermediaries who ensure the enforceability of inheritance rights through authentic documentation. It concludes that heirs’ legal protection must be strengthened by upholding the principles of legality and substantive justice within the financial sector.